Integrating RADEC Model and AI to Enhance Science Literacy: Student Perspectives - Wati Sukmawati; Sintha Wahjusaputri (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to evaluate the use of the RADEC Model supported by Artificial Intelligence (AI) in enhancing students' science literacy. The research methodology involves data collection through student questionnaires, which include questions related to their understanding of scientific concepts, contexts, and attitudes after using the RADEC Model. Data analysis employs descriptive statistical techniques to assess students' agreement levels regarding the provided statements. The results indicate that most students exhibit high levels of agreement regarding the effectiveness of the RADEC Model in enhancing their understanding of science concepts, boosting learning motivation, facilitating problem-solving, and developing critical thinking skills. Positive impacts are also observed in improving student engagement in collaborative discussions and increasing their interest in further exploration of science. This research makes a significant contribution by highlighting the importance of integrating AI technology into educational approaches to enhance students' science literacy, with broad implications for improving the quality of science education in the future. In conclusion, the integration of the AI-based RADEC Model is an innovative step to increase the effectiveness of science learning in elementary schools, so prospective elementary school teachers must be able to master this technology to provide personalized learning experiences and improve students' science literacy.